Learning from HIV-1 to predict the immunogenicity of T cell epitopes in SARS-CoV-2 - Ang Gao; Zhilin Chen; Assaf Amitai; Julia Doelger; Vamsee Mallajosyula; Emily Sundquist; Florencia Pereyra Segal; Mary Carrington; Mark M. Davis; Hendrik Streeck; Arup K. Chakraborty; Boris Julg (iScience, 2021)
Summary: We describe a physics-based learning model for predicting the immunogenicity of cytotoxic T lymphocyte (CTL) epitopes derived from diverse pathogens including SARS-CoV-2. The model was trained and optimized on the relative immunodominance of CTL epitopes in human immunodeficiency virus infection. Its accuracy was tested against experimental data from patients with COVID-19. Our model predicts that only some SARS-CoV-2 epitopes predicted to bind to HLA molecules are immunogenic. The immunogenic CTL epitopes across all SARS-CoV-2 proteins are predicted to provide broad population coverage, but those from the SARS-CoV-2 spike protein alone are unlikely to do so. Our model also predicts that several immunogenic SARS-CoV-2 CTL epitopes are identical to seasonal coronaviruses circulating in the population and such cross-reactive CD8+ T cells can indeed be detected in prepandemic blood donors, suggesting that some level of CTL immunity against COVID-19 may be present in some individuals before SARS-CoV-2 infection.